Modelling and simulations for tourism and hospitality an introduction - Baggio, Jacopo A. 1980-; Baggio, Rodolfo (Tourism essentials, 2020)
This book offers an essential introduction to the use of various modelling tools and simulation techniques in the domains of tourism and hospitality. It aims to encourage students, researchers and practitioners in tourism and hospitality to enhance and enrich their toolbox in order to achieve a better and more profound knowledge of their field"--